Overweight and Obesity among Palestinian Adults: Analyses of the Anthropometric Data from the First National Health and Nutrition Survey (1999-2000) - Ziad Abdeen; Christine Jildeh; Sahar Dkeideek; Radwan Qasrawi; Ibrahim Ghannam; Haleama Al Sabbah (Hindawi Limited, 2012)
Background. A cross-sectional survey was designed to provide a baseline data on the prevalence and distribution of overweight and obesity and their associations among adults in Palestine. Methods. A random representative sample of 3617 adults aged 18-64 years was collected between October 1999 and October 2000. Results. The prevalence of overweight was 35.5% in women and 40.3% in men, obesity was 31.5% in women and 17.5% in men. Adults aged 45-54 years old were significantly more likely to be obese (29.2% in men and 50.2% in women) or overweight (48.1% in men and 37.2% in women). When compared with women, men showed significantly more normal BMI level (40.5% versus 31.6%; P<0.05). Cut-off points for a high waist circumference and high waist-to-hip ratio identified 57.8% and 47.2% of the population, respectively, to be at an increased and high risk for cardiovascular disease. Sociodemographic factors (age, sex, educational level, and marital status) were also found to be significantly related to BMI. Conclusion. Obesity and overweight are enormous public health problems in Palestine. Population-based research at the national level to investigate the social and cultural factors associated with high prevalence of overweight and obesity among Palestinian adults should be implemented.